Breast cancer prognosis and P-cadherin expression: systematic review and study-level meta-analysis. Issue Volume 12:Issue e6(2022) (17th September 2020) - Qi, Runzhi; Lin, Jinyin; Chen, Shuntai; Jiang, Juling; Zhang, Xing; Yao, Bo; Zheng, Honggang; Jin, Zhichao; Yuan, Yuan; Hou, Wei; Hua, Baojin; Guo, Qiujun
Abstract : Objective: P-cadherin can act both as a tumour suppressor and an oncogene. The clinical prognostic value of P-cadherin overexpression in breast cancer (BC) remains unclear. We conducted a study-level meta-analysis to determine whether P-cadherin expression can help predict prognosis in BC. Methods: A systematic literature search was performed to review eligible studies and clarify the relationship between P-cadherin overexpression and overall survival (OS), disease-free survival (DFS), pathological features, molecular subtypes and molecular phenotypes in BC. Results: Thirty-one studies including 12 332 patients were included. P-cadherin overexpression was correlated with significantly worse OS (HR=1.77, p<0.00001) and DFS (HR=1.96, p < 0.00001) than P-cadherin-negative. P-cadherin overexpression could lead to high histological grade (OR=3.33, p<0.00001) and lymph node metastasis (OR=1.62, p<0.00001). Moreover, P-cadherin overexpression was associated with low odds of the luminal A subtype and high odds of the human epidermal growth factor receptor-2 (HER2)-positive and triple-negative subtypes. P-cadherin expression led to low expression of oestrogen and progesterone receptor (OR=0.37 and OR=0.36, respectively, both p<0.00001) and high expression of HER2 (OR=2.31, p<0.00001), Ki-67 (OR=2.79, p<0.00001), epidermal growth factor receptor (OR=5.85, p<0.00001) and cytokeratin 5/6 (OR=6.79, p<0.00001). Conclusions: P-cadherin was found to be associated with invasiveness and metastasis. P-cadherin expression can probably be a useful biomarker for predicting poor survival and may act as an independent prognostic predictor.